Neoangiogenesis in prostate cancer - Łuczyńska, Elżbieta; Anioł, Joanna (Contemporary Oncology/Współczesna Onkologia, 2013)
Prostate cancer has the second highest incidence among malignant tumors in men in Poland, and the first in the USA. Currently, medical reports state that incidentally non-diagnosed prostate cancer is present in about 30–46% of men over the age of fifty. Tumor angiogenesis has significant implications in the diagnosis and treatment of various solid tumors. With fast, multi-slice CT scanners and their ability of qualitative and quantitative analysis of tumor angiogenesis, CT perfusion has been the subject of extensive investigation in the past twenty years. Tumor angiogenesis is characterized morphologically by an increase in the number of blood vessels including new capillaries, capillary sprouts, non-endothelialized capillaries and arterio-venous shunts. It is stated in the literature that pathological vessel density within prostate cancer is one of the factors determining the extent of the tumor – whether the tumor is confined to the prostate gland or extends beyond the prostate capsule. It was proved that the density of pathological vessels is higher in patients with tumors beyond the prostate capsule. Initial publications show validity of functional imaging, such as perfusion CT in prostate cancer staging before a surgical procedure. This examination can also show excessive density of pathological vessels within the prostate gland according to increased blood volume (BV) and blood flow (BF) and pathologically increased permeability of the vessels (PS). Vessel abnormalities in the examined area are also indicated by shorter mean transit time (MTT).